Gas exchange and fluorescence of Brosimum alicastrum - Hernández-González, Olivia; Vergara-Yoisura, Silvia; Sulub-Tun, Roger; Castillo-Chuc, José Manuel; Larque-Saveedra, Francisco Alfonso (REVISTA TERRA LATINOAMERICANA, 2019)
Gas exchange measurements were taken with an infrared gas analyzer (IRGA) and chlorophyll fluorescence with a modulated amplitude pulse fluorimeter (Mini-PAM) on fully developed leaves of ramon (Brosimum alicastrum Swartz) a tropical rainforest tree, grown in its natural habitat as to collect basic information of its physiological behavior. Data showed that maximum f ixation of CO2 was 5 µmol m-2 s-1, photosynthetic eff iciency was 0.67 while the photosystem II was found to saturate at a photonic flux density (PFD) of 500 µmol at 15 h. A high correlation was found between photosynthesis and transpiration. Highest water use eff iciency occurred after 15 hours at a temperature of 30 °C, while chlorophyll levels remained constant. This is a shade tolerant, plant species thus it was found that initiates the photosynthetic process with low levels of light, presenting a light compensation point of 24 µmol m-2 s-1. In a parallel study, the same variables were measured in two sets of individuals of the same specie collected from two distant localities but growth in pots in the open. Photosynthetic variables of this plant species data showed very similar patterns. The results obtained suggest that, during the daylight hours and at higher temperatures, this species can carry out photosynthesis with high water use eff iciency. Based on the results, the conclusion is that this plant species can adapt to a diversity of environmental conditions.